STUDENT SELF-DEVELOPMENT THROUGH KAMPUS MENGAJAR ANGKATAN 1 PROGRAM AT SDIT MADANI EKSELENSIA SIDOARJO - Vanda Rezania; Jamilatur Rohmah (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2021)
The Kampus Merdeka Angkatan 1 Program has been held at the target elementary school, namely SDIT Madani Ekselensia Sidoarjo from March to June 2021. This program is part of the Merdeka Campus which involves students from various universities in Indonesia and educational backgrounds to assist the teaching and learning process in elementary schools. which is accredited C and provides opportunities for students to be able to learn and develop themselves through activities outside the lecture class. The Kampus Merdeka Angkatan 1 Program at SDIT Madani Ekselensia aims to help optimize elementary education services during the pandemic. This program involves eight students selected to devote themselves to SDIT Madani Ekselensia who come from various educational backgrounds, including from Guidance and Counseling study programs, State Administration Science, PGSD, Electrical Engineering, Japanese Language Education, and Management. This program contributes to increasing student empathy and sympathy as well as student teaching skills